Local Electrical Imaging of Tetragonal Domains and Field-Induced Ferroelectric Twin Walls in Conducting SrTiO3 - COEY, JOHN (My University, 2016)
We demonstrate electrical mapping of tetragonal domains and electric field-induced twin walls in SrTiO 3 as a function of temperature and gate bias utilizing the conducting LaAlO 3 = SrTiO 3 interface and low-temperature scanning electron microscopy. Conducting twin walls appear below 105 K, and new twin patterns are observed after thermal cycling through the transition or on electric field gating. The nature of the twin walls is confirmed by calculating their intersection angles for different substrate orientations. Numerous walls formed when a large side- or back-gate voltage is applied are identified as field-induced ferroelectric twin walls in the paraelectric tetragonal matrix. The walls persist after switching off the electric field and on thermal cycling below 105 K. These observations point to a new type of ferroelectric functionality in SrTiO 3 , which could be exploited together with magnetism and superconductivity in a multifunctional context
Keywords: electrical mapping of tetragonal domains; electrical mapping of tetragonal domains